DETECTION OF SOMEONE'S CHARACTER BASED ON FACE SHAPE USING THE CANNY METHOD - Zunita Wulansari; Taofik Chulkamdi (Universitas Islam Balitar, 2021)
Character is a unique way of interacting by individuals in creating a relationship. When interacting with people, it requires us to be face to face. The face is a very important element in communicating because from the face we can see a person's expression and the person's facial pattern so that their character can be known. The face is considered a reflection of a person's character so that a science called physiognomy has emerged. Physiognomy science is usually only known by experts, to get an easier way, technology can help provide solutions. The solution is to use a camera by taking a picture of the face whose character you want to understand, then doing a digital image processing (PCD). In this PCD process, there are several processes for processing images in order to obtain information from the image. One way is to use canny edge detection. Canny edge detection is used to identify or recognize object boundary lines in the image after the canny edge detection process is completed. The next process is to recognize face patterns by adding the euclidean distance method so that the face shape pattern can be recognized. The results of facial recognition test using the Canny and Euclidean distance method from 40 facial images, the percentage of success is 80%.